A Measure of Capacity Contribution of Static Mono-Si Photovoltaic Systems - Varnavas, Constantinos (2013)
Photovoltaic (PV) systems generate electricity in the daytime when system demand is generally moderate to high. For Mediterranean countries, there is also seasonal coincidence of high system demand and high PV load factors. The present study quantifies the above statements by calculating the load factor of the PV system when system demand is high (above 90–99% of the maximum demand of the month). The percentage of time the PV load factor is above 90% for these periods of maximum demand is evaluated. The PV load capacity contribution is defined in this study as the minimum PV load factor during these periods of high demand. Actual generation data from a static (without tracking) mono-Si PV system, recorded every half hour for the year 2010 are compared to system demand data. The seasonality analysis indicates that PV contribution to capacity is only significant during the months May–October. For the months November–April, when daily demand peak occurs during the evening, PVs do not contribute towards capacity. The evaluated capacity contribution of PV systems depends on the threshold of maximum demand considered (90%–99%). For the threshold of 95%, the capacity contribution for May–October ranges between 27%–41% of PV installed capacity.